2015
DOI: 10.4103/2231-4040.150368
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of linagliptin and metformin by reverse phase-high performance liquid chromatography method: An application in quantitative analysis of pharmaceutical dosage forms

Abstract: To enhance patient compliance toward treatment in diseases like diabetes, usually a combination of drugs is prescribed. Therefore, an anti-diabetic fixed-dose combination of 2.5 mg of linagliptin 500 mg of metformin was taken for simultaneous estimation of both the drugs by reverse phase-high performance liquid chromatography (RP-HPLC) method. The present study aimed to develop a simple and sensitive RP-HPLC method for the simultaneous determination of linagliptin and metformin in pharmaceutical dosage forms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In addition, several methods were reported for the simultaneous quantitation of LIG and MEF in pure form, in pharmaceutical dosage form, or in human plasma. These methods include spectrophotometry (Rajendran, 2019), HPLC (Jadhav et al, 2016;Jadhav et al, 2017;K et al, 2019;Prasanna et al, 2015;Sivagami et al, 2020;Swamy & Baba, 2013;Vemula et al, 2015), HPTLC (Rajasekaran et al, 2014;Srivani et al, 2016), or LC-MS/MS (Abbas Moussa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several methods were reported for the simultaneous quantitation of LIG and MEF in pure form, in pharmaceutical dosage form, or in human plasma. These methods include spectrophotometry (Rajendran, 2019), HPLC (Jadhav et al, 2016;Jadhav et al, 2017;K et al, 2019;Prasanna et al, 2015;Sivagami et al, 2020;Swamy & Baba, 2013;Vemula et al, 2015), HPTLC (Rajasekaran et al, 2014;Srivani et al, 2016), or LC-MS/MS (Abbas Moussa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The empirical formula is C 25 H 28 N 8 O 2 and the molecular weight is 472.54 g/mol [ 14 ]. In the available literature, we can only find information about some structures of the resulting degradants [ 15 , 16 , 17 ]. There is a lack of information on a comprehensive analysis of degradation products, as well as proposed structures for the identified impurities.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of information on a comprehensive analysis of degradation products, as well as proposed structures for the identified impurities. Several studies have been conducted on the assessment of linagliptin through liquid chromatography methods, encompassing both HPLC and UPLC, in conjunction with UV or PDA detectors [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, there are not many papers related to the identification of impurities.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature review it was found that, many analytical techniques have been reported for the determination of EMP and LIN, including UV spectrophotometry (Amrutiya et al, 2017;Ayoub, 2016;Cholke et al, 2019;Padmaja & Veerabhadram, 2015), voltammetry (Naccar, Saleh, Omar, Haredy, & Derayea, 2020), HPTLC (Bhole, Wankhede, & Pandey, 2017;Thakor, Amrutkar, & Chaudhari, 2019), HPLC (Abdel-Ghany, Ayad, & Tadros, 2018Al-Sabti & Harbali, 2020;Attimarad, Nagaraja, Aldhubaib, Nair, & Venugopala, 2014;Basak, Gouru, Bera, & Nagappan, 2019;Donepudi & Achanta, 2018;El-Bagary, Elkady, & Ayoub, 2013;Ganorkar, Askarkar, Gupta, & Milind, 2020;Geetha Swarupa, Lakshmana Rao, Prasad, & Suresh Babu, 2016;Gholami, Bahrami, & Faraji, 2020;Manoel et al, 2020;Naazneen & Sridevi, 2016;Padmaja & Veerabhadram, 2017;Rajbangshi, Alam, Hossain, Islam, & Rouf, 2018;Salapaka et al, 2019;Sharif et al, 2020;Supriya Reddy, Chandan, Sai Charan, & Akshay, 2020;Vemula, Dodda, Balekari, Panga, & Veeresham, 2015;Wattamwar, Mungantiwar, Halde, & Pandita, 2020;Yadav, Dornala, Swain, Prabha, & Samanthula, 2020), UPLC (Ayoub, 2015;Dubey, Singh, Tyagi, Bhardwaj, & Raghav, 2014;Jagadabi, Kumar, Pamidi, Ramaprasad, & Nagaraju, 2018;Madana Gopal & Sridhar, 2017;Nannapaneni, Jalalpure, Muppavarapu, & Sirigiri, 2016)…”
Section: Introductionmentioning
confidence: 99%